MATURE TERATOMA OF THE FALLOPIAN TUBE - Sabit, Katerina Kubelka; Filipovski, V; Sardzovski, Boban; Dzingis, Jasar (Journal of Morphological Sciences, 2018)
Teratomas of fallopian tube are extremely rare tumors with less than 80 cases reported in the literature. The majority of reported tumors are benign and show great variation in size. We present a case of mature teratoma of the left fallopian tube occurring as a synchronous neoplasm in a 41-years old patient, surgically treated for invasive squamous cell cervical cancer. Although the incidence of fallopian tube teratomas is low, awareness of its existence is necessary, since their occurrence can sometimes lead to serious complications.